2015
DOI: 10.1002/2014jc010677
|View full text |Cite
|
Sign up to set email alerts
|

Arctic sea ice and freshwater sensitivity to the treatment of the atmosphere‐ice‐ocean surface layer

Abstract: Global simulations are presented focusing on the atmosphere-ice-ocean (AIO) surface layer (SL) in the Arctic. Results are produced using an ocean model (NEMO) coupled to two different sea ice models: the Louvain-La-Neuve single-category model (LIM2) and the Los Alamos multicategory model (CICE4). A more objective way to adjust the sea ice-ocean drag is proposed compared to a coefficient tuning approach. The air-ice drag is also adjusted to be more consistent with the atmospheric forcing data set. Improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 65 publications
2
42
0
Order By: Relevance
“…The mean ice thickness in H05 is closer to the ICESat observations, but there is a region of overestimated thickness in the Beaufort Gyre and an underestimation elsewhere which is consistent with our findings from the ice mass balance and ULS measurements and also with results of Roy et al (2015). Finally, the domain total ice volume of the different model simulations is compared to the estimate of the dataassimilative model PIOMAS (Zhang and Rothrock, 2003).…”
Section: Ice Concentration Thickness and Volumesupporting
confidence: 86%
See 3 more Smart Citations
“…The mean ice thickness in H05 is closer to the ICESat observations, but there is a region of overestimated thickness in the Beaufort Gyre and an underestimation elsewhere which is consistent with our findings from the ice mass balance and ULS measurements and also with results of Roy et al (2015). Finally, the domain total ice volume of the different model simulations is compared to the estimate of the dataassimilative model PIOMAS (Zhang and Rothrock, 2003).…”
Section: Ice Concentration Thickness and Volumesupporting
confidence: 86%
“…Following Roy et al (2015) for our last two hindcasts and because our first ocean layer thickness is relatively small, the ice-ocean drag coefficient is computed by a log-layer assumption using the oceanic first layer thickness and a roughness length scale of 0.03 m as suggested by Maykut and McPhee (1995) which yields a drag coefficient of 2.32 × 10 −2 . The air-ice stress involves a more sophisticated formulation that takes into account the stability of the atmospheric boundary layer.…”
Section: Lim2 and Cice Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, higher-resolution regional coupled atmosphere-ocean-ice models are providing improved skill and starting to be used operationally (Pellerin et al, 2004;Smith et al, 2013); while climate and Earth system models are also increasing in resolution and these will all require accurate surface exchange over the MIZ. Recent ocean-ice and atmosphere-ocean-ice modelling studies have demonstrated considerable sensitivity to surface exchange parametrisation over sea ice, particularly in their simulations of sea-ice thickness and extent (Tsamados et al, 2014;Rae et al, 2014) and the polar ocean (Stössel et al, 2008;Roy et al, 2015). Sim-…”
Section: Introductionmentioning
confidence: 99%